Influéncia da adubação nitrogenada sobre a interferéncia de plantas daninhas em feijoeiro1 - Bressanin, Fernanda Nunes [UNESP]; Nepomuceno, Mariluce [UNESP]; Martins, José Valcir Fidelis [UNESP]; de Carvalho, Leonardo Bianco; Alves, Pedro Luis da Costa Aguiar [UNESP] (FapUNIFESP (SciELO), 2013)
The competition between weeds and bean plants, especially because of nutrients in the environment, is extremely important to minimize potential losses of crop productivity. Thus, the aim of this work was to evaluate the effects of using nitrogen fertilization on the timing and extent of the period before interference (PAI), total period of interference (PTPI) and the critical period of interference control (PCPI) in bean cultivar 'Ruby'. The seeds were sown in the conventional system and the trial was conducted in two areas at the same time, in which the nitrogen fertilization was performed only in one of them. Each area received 14 treatments consisting of two groups: first, the crop was free of interference of weeds from emergence to 10, 20, 30, 40, 50, 60 and 70 days; and the second: the crop remained free of interference from sowing to the same periods described above. The experimental design was randomized blocks with four replications. Raphanus raphanistrum showed greater relative importance in the two areas, mainly due to the accumulation of dry mass, followed by Amaranthus deflexus. There was no difference in diversity and evenness of weed populations in response to the fertilization. In the area without N PAI occurred 18 days after emergence (DAE), and up to 24 DAE PTPI, resulting in PCPI 18 to 24 DAE, this area had 58% of reduction in crop yield. In the area where with nitrogen fertilization, PAI occurred at 38 DAE and PTPI occurred at 19 DAE. In this area there was 56% of reduction in crop yield. The nitrogen fertilization increased crop productivity and favored competitiveness in relation to weeds.
Period of weed interference in bean with nitrogen fertilizer
Keywords: Competition; Nitrogen.; Phaseolus vulgaris L.; Weed